Evaluation of Death Anxiety in Elderly Patients With Cancer Undergoing Chemotherapy - Farideh Bastani; Fattaneh Farnood; Hamid Haqhani (Iran University of Medical Sciences, 2016)
Background: Aging population and prevalence of diseases like cancer among them have affected general health of the elderly, so that one of the influential factors on health components of elderly patients with cancer is death anxiety, which has important consequences in them. Methods: In this cross-sectional (descriptive correlational) study, 130 elderly patients with cancer undergoing chemotherapy were recruited by convenience sampling method. To collect information, demographic information form and Templer's death anxiety inventory were used. To analyze the data, descriptive statistics, statistical tests were used through SPSS 21. Results: The results showed that 42.3% of the old people had high death anxiety. The mean (SD) score of death anxiety was found 6.85 (2.7) which was at the desirable level. In this study, death anxiety of old people had significant relationship with variables of age (P<0.001), marital status (P<0.012), education level (P<0.001), cancer type (P<0.023), period of suffering from cancer (P<0.018), and other comorbid diseases (P<0.001). So that old people with lower age, higher level of education, married, lower period of cancer, and without underlying diseases, had lower death anxiety. Conclusion: The results of this study can be a basis for better understanding of educational, consultation, and supporting needs regarding coping with anxiety and its management (based on the culture of the community) in this group of elderly patients with cancer.